2016
DOI: 10.1130/ges01217.1
|View full text |Cite
|
Sign up to set email alerts
|

Paleomagnetic record determined in cores from deep research wells in the Quaternary Santa Clara basin, California

Abstract: Paleomagnetic study of cores from six deep wells provides an independent temporal framework for much of the alluvial stratigraphy of the Quaternary basin beneath the Santa Clara Valley. This stratigraphy consists of 8 upward-fining cycles in the upper 300 m of section and an underlying 150 m or more of largely fine-grained sediment. The eight cycles have been correlated with the marine oxygen isotope record, thus providing one means of dating the section. The section has also proved to contain a rich paleomagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 110 publications
0
2
0
Order By: Relevance
“…2.3.1 Site 1: Guadalupe River, San Jose, CA, USA Site 1 overlaps with the location of drill hole 006S001W26Q001 (longitude − 121.93505°, latitude 37.37770°) (Wentworth et al 2015;Mankine and Wentworth 2016). Wentworth et al (2015) and Mankine and Wentworth (2016) interpreted data from the drill hole and showed that a 407-m-thick strata of Quaternary sediments overlies a bedrock of late-Mesozoic Franciscan Group consisting of metamorphic sandstones.…”
Section: Goals Of the Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…2.3.1 Site 1: Guadalupe River, San Jose, CA, USA Site 1 overlaps with the location of drill hole 006S001W26Q001 (longitude − 121.93505°, latitude 37.37770°) (Wentworth et al 2015;Mankine and Wentworth 2016). Wentworth et al (2015) and Mankine and Wentworth (2016) interpreted data from the drill hole and showed that a 407-m-thick strata of Quaternary sediments overlies a bedrock of late-Mesozoic Franciscan Group consisting of metamorphic sandstones.…”
Section: Goals Of the Trialsmentioning
confidence: 99%
“…2.3.1 Site 1: Guadalupe River, San Jose, CA, USA Site 1 overlaps with the location of drill hole 006S001W26Q001 (longitude − 121.93505°, latitude 37.37770°) (Wentworth et al 2015;Mankine and Wentworth 2016). Wentworth et al (2015) and Mankine and Wentworth (2016) interpreted data from the drill hole and showed that a 407-m-thick strata of Quaternary sediments overlies a bedrock of late-Mesozoic Franciscan Group consisting of metamorphic sandstones. The upper 300 m of sediments shows eight cycles of coarse through fine sediments; a coarse unit of gravels at base of cycle 3 (depth range 103-116 m) serves as a marker separating slower V S above and faster V S below, as seen on the shear-wave borehole log of Fig.…”
Section: Goals Of the Trialsmentioning
confidence: 99%